The dynamics of stress: a longitudinal MRI study of rat brain structure and connectome. Issue 10 (October 2018) - Magalhães, R; Barrière, D; Novais, A; Marques, F; Marques, P; Cerqueira, J; Sousa, J; Cachia, A; Boumezbeur, F; Bottlaender, M; Jay, T; Mériaux, S; et al.
Abstract Stress is a well-established trigger for a number of neuropsychiatric disorders, as it alters both structure and function of several brain regions and its networks. Herein, we conduct a longitudinal neuroimaging study to assess how a chronic unpredictable stress protocol impacts the structure of the rat brain and its functional connectome in both high and low responders to stress. Our results reveal the changes that stress triggers in the brain, with structural atrophy affecting key regions such as the prelimbic, cingulate, insular and retrosplenial, somatosensory, motor, auditory and perirhinal/entorhinal cortices, the hippocampus, the dorsomedial striatum, nucleus accumbens, the septum, the bed nucleus of the stria terminalis, the thalamus and several brain stem nuclei. These structural changes are associated with increasing functional connectivity within a network composed by these regions. Moreover, using a clustering based on endocrine and behavioural outcomes, animals were classified as high and low responders to stress. We reveal that susceptible animals (high responders) develop local atrophy of the ventral tegmental area and an increase in functional connectivity between this area and the thalamus, further spreading to other areas that link the cognitive system with the fight-or-flight system. Through a longitudinal approach we were able to establish two distinct patterns, with functional changes occurring during the exposure to stress, but with an inflection point after the first week of stress when more prominent changes were seen. Finally, our study revealed differences in functional connectivity in a brainstem–limbic network that distinguishes resistant and susceptible responders before any exposure to stress, providing the first potential imaging-based predictive biomarkers of an individual's resilience/vulnerability to stressful conditions.